Environmental and behavioral mitigation strategies for patients with atopic dermatitisCapsule Summary - Nadia Shobnam, MD; Grace Ratley, MSPH; Jordan Zeldin, BS; Manoj Yadav, PhD; Ian A. Myles, MD, MPH (Elsevier, 2024)
Objective: Herein, we aimed to summarize the evidence-base for these interventions with a focus on the role of specific chemicals in driving AD. Methods: A narrative review of nonprescription mitigation strategies in AD was conducted. Results: We identified avoidance strategies for the various routes of exposure such as air pollution, water contamination, or inclusion in home goods, skin care products, and cleansers. Evidence for and against dietary modification and emollient use as primary prevention were also elucidated. To remember these interventions we propose a mnemonic, HELPSS AD: Home decor, Emollients, Laundering, Probiotics, Soaks, Social support, Air quality, and Diet. Limitations: Each of these categories presents nuanced molecular differences that must be considered. For example, probiotic responses vary by the specific species while home products and pollution must be analyzed by the specific toxins. Conclusion: Although the interventions discussed lack the level of evidence required for inclusion into formal guidelines, awareness of these approaches may offer aid to, and build trust with, patients and caregivers.